Fracturing Debate? A Review of Research on Media Coverage of “Fracking” - Matthews, Julian; Hansen, Anders (Frontiers in Communication, 2018)
Hydraulic fracturing is an energy extraction process that is increasingly attracting controversy. This article seeks to outline how the media report hydraulic fracturing (or ‘fracking’), and to explore its place within the reporting of energy concerns generally. To this end, it draws on an environmental communication perspective to understand media coverage of the issue and the processes that shape it. This review reveals that media coverage of fracking is partitioned according to discussions of the economic benefits or the environmental risks associated with the process. Further, these observed patterns in the coverage appear to mirror the recognised claims made about the issue and the influence from national polity on energy production and security. While there is evidence that news organisations and journalism mediate what is reported, their readers appear largely ambivalent or undecided on the issue at present. Therefore, it is argued that future research must continue to examine the coverage of hydraulic fracturing, its context, production and wider reception to develop our understanding of the role of the media in national conversations on fracking, energy and the environment.